Adherence to airway clearance therapy in pediatric cystic fibrosis: Socioeconomic factors and respiratory outcomes. Issue 12 (5th October 2015) - Oates, Gabriela R.; Stepanikova, Irena; Gamble, Stephanie; Gutierrez, Hector H.; Harris, William T.
Summary: Objectives: The evidence linking socioeconomic status (SES) and adherence in cystic fibrosis (CF) is inconclusive and focused on medication uptake. We examined associations between SES, adherence to airway clearance therapy (ACT), and CF respiratory outcomes. Study Design: Socioeconomic, clinical, and adherence data of CF patients (N = 110) at a single CF Center were evaluated in this cross‐sectional observational study. SES was operationalized as maternal and paternal education and household income. Adherence to ACT was measured with utilization data from the high‐frequency chest wall oscillation (HFCWO) device over 4–6 weeks. Statistical modeling was used to test three hypotheses: (H1) Higher SES is associated with higher ACT adherence; (H2) Higher SES is associated with better respiratory outcomes; and (H3) ACT adherence mediates the relationship between SES and respiratory outcomes. Results: In multinomial logistic regression, maternal college education, annual income >$50, 000, and more adults in the household were independently related to better adherence ( P  < 0.05). Paternal college education, income >$100, 000, and lack of exposure to smoking were independently related to higher lung function ( P  < 0.05). Current adherence to ACT with HFCWO was not associated with lung function over 12 months. Conclusions: SES is associated both with ACT adherence and respiratory outcomes in pediatric CF patients. However, the link between SES and respiratory outcomes in this study was not mediated by adherence to ACT with HFCWO. These data emphasize the importance of socioeconomic resources and household environment for CF health. Family socio‐demographic profiles can help identify patients at increased risk for ACT nonadherence.Pediatr Pulmonol. 2015; 50:1244–1252. © 2015 Wiley Periodicals, Inc.